PENGARUH DAUN LEMBAYUNG TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU MENYUSUI - Septa Dwi Insani; Husna Sari; Mutiara Dwi Yanti; Naimah Nasution; Tedty Rohaya Tinambunan; Wahyuna L. Samosir (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2022)
Mother Breastmilk is the most beautiful gift from mother to baby which contains essential substances that have the best nutrition and high energy that is easily digested and available at any time and is not found in any food or drink, both in the most expensive and best formula milk. . Lembayung leaf or long bean leaf is one type of vegetable that can be consumed in a young state, the whole fruit and its seeds and leaves are useful for vegetables, treatment and healing of several types of diseases and can increase breast milk production. The purpose of this study was to determine the effect of giving lavender leaves on increasing breast milk production for breastfeeding mothers by assessing the baby's development as seen from tub duration, tub characteristics, chapter duration, tub color, sleep pattern, and baby's body weight, before and after the procedure. administration of lavender leaves as much as 200 grams / day for one week. The method in this study is a quasi-experimental research design with One-Group Pretest-Posttest Design or Group Pretest-Posttest, and the sampling technique in this study is the Accidental Sampling technique, which is a sampling technique based on chance. The total population in this study was 26 people and the number of samples in this study was 19 people. The results in this study indicate that there is an increase in breast milk production after the administration of processed lavender leaves which can be seen from 6 characteristics including: tub duration, tub characteristics, chapter duration, tub color, sleep pattern, and baby weight differences before treatment on breastfeeding mothers and after treatment with p value = 0.000 < from a value (0.05). It is hoped that all breastfeeding mothers can increase their knowledge and insight in increasing breast milk production.